Reviews - Liversage, David; Koch, Eva; Holch, Per; Bender, Lise; Hårdh, Britta (Journal of Danish Archaeology, 1986)
Magdalena S. Midgley: The Origin and Function of the Earthen Long Barrows of Northern Europe (by D. Liversage). Ben A. Nelson (ed.): Decoding Prehistoric Ceramics (by Eva Koch Nielsen). Pia Bennike: Palaeopathology of Danish Skeletons (by Per Holch). Inga Hagg: Die Textilfonde aus dem Hafen von Haithabu (by Lise Bender Jorgensen). Else Roesdahl: Viking Age Denmark (by Birgitta Hardh).